Passive and Active Control on 3D Convective Flow of Viscoelastic Nanofluid With Heat Generation and Convective Heating - Eswaramoorthi, S.; Bhuvaneswari, M. (Frontiers in Mechanical Engineering, 2019)
The present article addresses the impact of passive control (PC) and active control(AC) on 3D flow of a viscoelastic nanofluid upon a stretching plate including heat generation and convective heating. The system of appearing non-linear PDE’s are converted into a couple of ODE’s by using suitable similarity transformations. Convergent series solutions are derived using homotopy analysis method (HAM). Graphical results of velocity, nanoparticle volume fraction and temperature of different pertinent physical parameters with notable discussions are pointed with their physical significance